An Empirical Study of Faculty Satisfaction and Its Impact on Retention - N Malati; Pratiksha Tiwari, and Swati Jain (Abhigyan, 2012)
Faculty is the core asset for every institution and its satisfaction becomes primarily important for the sustainability and growth of the institution. In the current times when there exits opportunities galore for qualified faculty, the institutions’ have to understand the importance of faculty satisfaction and also comprehend the various factors which affect satisfaction so as to ensure better performance and retention too. Four factors were identified for the study- work environment, compensation, training and development and role of HOD. It has been observed that training and development has been ranked as the major factor for the faculty intending to stay in an institution. In addition the paper attempts to understand the significance of the parameters and their relationship with each other.